Enhancing Accessibility in Public Spaces: A Computational Study of Hatirjheel Lakefront Using Space Syntax - Sharif Tousif Hossain; Baqer Al-Ramadan; Muhammad Bilal; Hamad Ahmed Altuwaijri (ISPRS International Journal of Geo-Information)
Public spaces are vital for urban living, contributing to the environmental, social, and economic aspects of city life. Hatirjheel Lakefront, a newly developed recreational area in Dhaka, offers significant potential for enhancing accessibility and connectivity in a rapidly urbanizing metropolis. This study aims to evaluate global and local integration of access routes and propose strategies to improve pedestrian and vehicular connectivity using Space Syntax methodology and DepthmapX V10 software. The key findings indicate that while Hatirjheel demonstrates strong global integration, regional integration remains moderate, with certain access roads being underutilized due to poor connectivity. Recommendations include enhancing integration through connecting dead-end roads, improving pedestrian pathways, and constructing foot-over bridges to mitigate vehicular traffic barriers. This study contributes to urban planning by providing actionable insights to optimize accessibility in public spaces, supporting recreational and economic activities. The findings are critical for creating a more integrated urban fabric in Dhaka, ensuring sustainable urban growth. This research provides actionable strategies for urban planners to optimize the use of public spaces, reinforcing the role of Hatirjheel as a vital component of Dhaka’s urban network.